Data from: Origins and functional diversification of salinity-responsive Na+, K+ ATPase α1 paralogs in salmonids - Dalziel, Anne C.; Bittman, Jesse; Mandic, Milica; Ou, Michelle; Schulte, Patricia M. (Borealis, 2021)
AbstractThe Salmoniform whole-genome duplication is hypothesized to have facilitated the evolution of anadromy, but little is known about the contribution of paralogs from this event to the physiological performance traits required for anadromy, such as salinity tolerance. Here, we determined when two candidate salinity-responsive paralogs of the Na+, K+ ATPase α subunit (α1a and α1b) evolved and studied their evolutionary trajectories and tissue-specific expression patterns. We found that these paralogs arose during a small scale duplication event prior to the Salmoniform, but after the teleost, whole-genome duplication. The ‘freshwater paralog’ (α1a) is primarily expressed in the gills of Salmoniformes and an unduplicated freshwater sister-species (Esox lucius), and experienced positive selection in the fresh-water ancestor of Salmoniformes and Esociformes. Contrary to our predictions, the ‘saltwater paralog’ (α1b), which is more widely expressed than α1a, did not experience positive selection during the evolution of anadromy in the Coregoninae and Salmonine. To determine if parallel mutations in Na+, K+ ATPase α1 may contribute to salinity tolerance in other fishes, we studied independently evolved salinity-responsive Na+, K+ ATPase α1 paralogs in Anabas testudineus and Oreochromis mossambicus. We found that a quarter of the mutations occurring between salmonid α1a and α1b in functionally important sites also evolved in parallel in at least one of these species. Together, these data argue that paralogs contributing to salinity tolerance evolved prior to the Salmoniform whole-genome duplication and that strong selection and/or functional constraints have led to parallel evolution in salinity-responsive Na+, K+ ATPase α1 paralogs in fishes., Usage notesKey for Figure 2Accession numbers for all sequences used in Figure 2 and the short name used in sequence files for PAML and alignments (Appendix S1).Fig2_SequenceIDs_to_GenbankNumbers.txtFig4- Pike real time dataGene expression of Na+, K+ ATPase paralogs and 18S in the Northern Pike (Esox lucius)Fig4_Pike real time datal.xlsSupplementary Fig1Teleost Na+, K+ ATPase α1 (ATP1A1) gene tree reconstructed using Bayesian inference (BI) with MrBayes version 3.2.1 (Ronquist et al. 2012) and the GTR+I+Γ model of nucleotide evolution.SuppFig1_MrBayes_Jan_7_2013.rtfSupplementary Figure 2Teleost Na+, K+ ATPase α1 (ATP1A1) gene tree reconstructed using the maximum likelihood (ML) method with RAxML software version 7.2.7 (Stamatakis 2006) and the GTR+Γ model of nucleotide evolution.SuppFig2_RAxML_Dec_30.rtfTree file for PAMLTree file to be used with the one and free ratios models in PAML (Table 1, Test 1a).ATP1A1.treesControl file for PAML - Branch ModelControl file for PAML branch model to test for selection along Branch D of Fig.2 (Table 1).BranchModel_BranchD.ctlTree file for PAML - 2Tree file for PAML's Branch-Site Model A (testing for selection along Branch D of Fig.2. Table 3)BranchModel_BranchD.treesControl file for PAML - Branch Null ModelControl file for the null PAML Branch Model testing for selection along Branch D in Figure 2 (Table 1).BranchModel_BranchDnull.ctlControl file for PAML - Branch-Sites ModelControl file for PAML`to run Branch-sites Model A along branch D in Figure 2 (Table 3).BranchSite_BranchD.ctlTree file for PAML - 3Tree file for PAML's Branch-Site Model A, testing for selection in sites along Branch D in Figure 2 (Table 3).BranchSite_BranchD.treesControl file for PAML Branch-Site Null ModelControl file for PAML's null Branch-site Model A testing for selection along Branch D in Figure 2 (Table 3).BranchSite_BranchDnull.ctlPAML control file - Free RatioControl file for PAML's Free-Ratios model (Table 1)FreeRatios.ctlPAML control file - Clade model C null (M2a_rel)Control file for the null model to PAML's Clade Model C (Table 2).M2a_rel.ctlPAML control file - Clade model CControl file for PAML's Clade Model C model testing for divergent selection among all a1a and a1b paralogs (Table 2, Test 2a).ModelC_a1a_a1b.ctlTree file for PAML- 4Tree file for PAML's clade Model C, to run Test 2a (Table 2).ModelC_a1a_a1b.treesPAML Control file - One-RatioControl file for PAML's One-Ratio model (Table 1)OneRatio.ctlPAML sequence fileSequence file to use during all PAML models. All 36 species from Figure 2 are included.Seq_ATP1A1.txt